2016
DOI: 10.1007/s12035-016-9951-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Metabolism Power SIRT2-Dependent Deficient Traffic Causing Alzheimer’s-Disease Related Pathology

Abstract: Multiple lines of evidence state a major role for mitochondrial dysfunction in sporadic Alzheimer's disease (AD) etiopathogenesis. However, the molecular mechanism(s) triggered by mitochondrial deficits that lead to neurodegeneration remain elusive. Herein, we propose a new mechanism by which mitochondrial loss of potential leads to a dysfunction in autophagy/mitophagy due to the overactivation of SIRT2, a tubulin deacetylase that regulates microtubule network acetylation, and provide insights into the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 77 publications
6
76
1
Order By: Relevance
“…The sirtuin family is comprised of seven sirtuins. Three of them have been confirmed to be the mitochondrial sirtuins that are closely related to the mitochondrial performance . Resveratrol has been indicated to upregulate SIRT1 expression, thereby protecting neurons from the Aβ aggregation‐induced toxicity.…”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…The sirtuin family is comprised of seven sirtuins. Three of them have been confirmed to be the mitochondrial sirtuins that are closely related to the mitochondrial performance . Resveratrol has been indicated to upregulate SIRT1 expression, thereby protecting neurons from the Aβ aggregation‐induced toxicity.…”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 98%
“…Three of them have been confirmed to be the mitochondrial sirtuins that are closely related to the mitochondrial performance. 161 Resveratrol has been indicated to upregulate SIRT1 expression, thereby protecting neurons from the Aβ aggregation-induced toxicity. It is shown that the antiinflammatory and antioxidant properties of resveratrol can delay the development of AD, and resveratrol can remarkably enhance mitochondrial autophagy.…”
Section: Sirtuinsmentioning
confidence: 99%
“…Recently, a SIRT2 polymorphism was associated with AD risk in different populations, providing evidence for the relationship between SIRT2 and AD from the perspective of genetics (Polito et al, 2013; Porcelli et al, 2013). Furthermore, SIRT2 mRNA levels increased in the peripheral blood of patients with AD (Wongchitrat et al, 2019), and SIRT2 levels escalated alongside the decreased acetylation of its recognized substrate α‐tubulin in the AD brain (Silva, Esteves, Oliveira, & Cardoso, 2016). Moreover, recent studies showed that the interference of SIRT2 mitigated AD‐like recognition deficits in both the mouse model of neurodegenerative diseases and the aged‐accelerated mouse model (Biella et al, 2016; Diaz‐Perdigon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously described that neurons may activate innate immunity in response to pathogen infection or to danger associated molecular patterns (DAMPs) [ 8 , 9 ]. Therefore, upon a given damage, mitochondria will present increased network fragmentation [ 10 ] expose DAMPs [ 11 ], which may be enough to activate neuronal innate immunity, with cytokine production to recruit and activate local microglia. The etiology of sporadic AD has been addressed by several different hypotheses such as the mitochondrial cascade hypothesis [ 12 ], the amyloid cascade hypothesis [ 13 ], the neuroinflammation hypothesis [ 14 ], and the infectious theory [ 15 ].…”
Section: Introductionmentioning
confidence: 99%